2005
DOI: 10.1242/jeb.01828
|View full text |Cite
|
Sign up to set email alerts
|

Venous tone and cardiac function in the South American rattlesnakeCrotalus durissus: mean circulatory filling pressure during adrenergic stimulation in anaesthetised and fully recovered animals

Abstract: venous tone, adrenaline as well as phenylephrine and isoproterenol (␣ ␣-and ␤ ␤-adrenergic agonists, respectively) were infused as bolus injections (2 and 10· g·kg -1 ). Adrenaline and phenylephrine caused large increases in MCFP and P CV , whereas isoproterenol decreased both parameters. This was also the case in fully recovered snakes. Therefore, adrenaline affects venous tone through both ␣ ␣-and ␤ ␤-adrenergic receptors, but the ␣ ␣-adrenergic receptor dominates at the dosages used in the present study. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
23
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 41 publications
8
23
0
Order By: Relevance
“…This recovery time was four-to fivefold faster than previously observed for a fish, Myoxocephalus scorpius, using similar techniques (Campbell et al, 2004). High fH values, similar to those observed immediately after CO 2 anaesthesia in our study, have been reported for snakes anaesthetised with pentobarbitone (Galli et al, 2005a;Galli et al, 2005b;Skals et al, 2005). In recovered rattlesnakes, equipped with flow probes and/or several vascular catheters, fH has previously been reported to be 25-30·beats·min -1 at 25°C (Skals et al, 2005), whereas values around 20·beats·min .…”
Section: Discussionsupporting
confidence: 87%
“…This recovery time was four-to fivefold faster than previously observed for a fish, Myoxocephalus scorpius, using similar techniques (Campbell et al, 2004). High fH values, similar to those observed immediately after CO 2 anaesthesia in our study, have been reported for snakes anaesthetised with pentobarbitone (Galli et al, 2005a;Galli et al, 2005b;Skals et al, 2005). In recovered rattlesnakes, equipped with flow probes and/or several vascular catheters, fH has previously been reported to be 25-30·beats·min -1 at 25°C (Skals et al, 2005), whereas values around 20·beats·min .…”
Section: Discussionsupporting
confidence: 87%
“…The mobilization of unstressed volume is primarily caused by venoconstriction, as the venous circulation holds approximately two-thirds of the total blood volume (Rothe, 1993;Sandblom and Axelsson, 2007). As the veins in pythons and other vertebrates are under adrenergic control, the shift from inactive to active blood volume is likely to reflect an increased sympathetic tone, consistent with studies on rattlesnakes, various fish and mammals that report an increase in both P CV and MCFP because of an α-adrenergic stimulation (Lillywhite, 1987;Pang, 2001;Sandblom and Axelsson, 2007;Skals et al, 2005). In addition to a sympathetic regulation of venous tone, it is an intriguing possibility that the expansion of the stomach upon ingestion of the large prey may reduce unstressed volume by squeezing the veins.…”
Section: Discussionsupporting
confidence: 75%
“…Pentobarbital anaesthesia does, however, mute autonomic regulation in reptiles (e.g. Crossley et al, 1998;Skals et al, 2005), and the typical withdrawal of parasympathetic tone is likely to explain the higher f H of the anaesthetized pythons than in previous studies on fully recovered pythons (Enok et al, 2012;Skovgaard et al, 2009). The lack of body movement during anaesthesia may also affect venous return, but will do so similarly in both groups and therefore have little effect on a comparison of cardiovascular parameters.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Sandblom et al, 2005;Skals et al, 2005Skals et al, , 2006Enok et al, 2016). By mobilizing blood from the veins, preload pressure may be maintained, or even increased, despite the increased heart rate during activity (Sandblom et al, 2005;Skals et al, 2006).…”
Section: Introductionmentioning
confidence: 99%